Development of short term hydrostatic test for PVC pipes - Mohamad Nabil, Nor Azman (2013)
This thesis deals with experimental design for the short term hydrostatic test for the Polyvinyl Chloride (PVC) pipes. The objective of this thesis is to design or develop an experimental setup in determining the burst pressure of a PVC pipes by the means of internal pressure. The thesis describes the experimental procedures to determine the burst pressure of the PVC pipes. The experimental value obtained is then compared to the theoretical value calculated from an existing formula. The samples used are designed using computer aided software which is SolidWork. The samples are then fabricated and tested based on the setup designed. From the result obtained, the value of experimental burst pressure is indeed different from the theoretical burst pressure.The result is then compared again with other formula basely for metal pipes in order to check the validity of the equations to be used for PVC pipes. Based on the result, the equations are not too suitable to be used as the different between the values from the main equation with the values calculated from other standard are too big. The result obtained from the experiment setup is also consistence as thus making a possible design to be proposed to the Department of Malaysian Standard as one of the test for the short term hydrostatic test in MS 628 standard.